Superior vena cava obstruction as manifestation of synovial cell sarcoma: a case report and review of literature - Dhiman, Pravesh; Patil, C. N.; Raghupathi, Renu (International Journal of Research in Medical Sciences, 2017)
Synovial cell sarcomas are one of the most common soft tissue tumors affecting adolescents and young adults. The common location of these tumors is often extremities. Primary involvement of mediastinum is a very rare presentation of this tumor, only few cases have been reported so far. We are reporting the case of a 27-year-old male patient who presented to us with a history of dyspnoea and chest discomfort of one week duration along with features of SVC obstruction. Chest is a frequently involved site of metastasis and lymphomas but rarely involved in synovial sarcoma. The learning point from this case is that rare causes like synovial sarcoma of mediastinum should always be included in differential diagnosis of mediastinal mass and SVC obstruction. We are reporting this case in view of its rarity. Though uncommon this case report emphasizes that synovial cell sarcoma should also be considered in differential diagnosis of mediastinal mass and early recognition with HPE, IHC and prompt institution of treatment can be lifesaving.